SISTEM PEMERINTAHAN INDONESIA MENURUT UUD 1945 (Suatu Kajian Teoritis) - W.M. Herry Susilowati (Perspektif, 2003)
There are two types of government system known nowadays, presidential and parliamentary. Its system is then stated into each country's constitution, while in Indonesia we know as UUD 1945. Referring to UUD 1945, Indonesia’s government system can’t be classified as presidential or parliamentary, but a combination of both system of UUD 1945 version.